Mathematics for Game Creators : Trionometry, vectors and matrices - Samyn, Koen, ....- (Wommelgem : Van In, 2024)
Mathematics for Game Creators. Trigonometry, vectors and matrices will cover the essential math principles and focus on the application in game engines and 3D editors.The author takes off by refreshing trigonometry fundamentals and elementary functions, to use them as a sound foundation to understand vectors. After a passage through aspects of and operations on vectors, already their dot and cross products enable a basic outline of lighting programming.Finally a sound initiation in kinematics and dynamics makes you knowledgeable in handling physics engines.
Keywords: Game development